Chemical characterization and development of anti-aging ingredients from Sclerocarya birrea and Ficus sycomorus - Maharaj, Vinesh J. (University of Pretoria, 2018)
Degradation of elastin and collagen in the extracellular matrix by elastase and collagenase accelerates skin aging. Phytochemicals that inhibit these enzymes can be developed as anti-aging ingredients. The anti-aging properties of Sclerocarya birrea (A. Rich.) Hochst (Marula) and Ficus sycomorus Linn (Sycamore) were investigated with the aim of developing chemically characterized anti-aging ingredients. The two plants were selected from the CSIR repository of extracts linked to traditional cosmetic use, extracts which had not been previously reported to have scientific data linked to anti-aging activity were selected. Young Marula soft wood stems, leaves and fruits collected from Kwazulu Natal and leaves of the Sycamore tree collected from Sodwana Nature Reserve were extracted using methanol:dichloromethane (DCM) (1:1). Results from the anti-collagenase and anti-elastase assays showed that Marula stems and leaves of the Sycamore were the most active. Extracts of the stems of Marula and leaves of the Sycamore tree have for the first time been scientifically proven to exhibit anti-elastase and anti-collagenase activities. Marula stems and Sycamore leaves harvested from the University of Pretoria experimental farm were extracted using acetone, ethanol, methanol:DCM (1:1) and sequentially using hexane, DCM, ethyl acetate and methanol and were screened in the anti-elastase and anti-collagenase assays. The results revealed that the ethanolic extract of both plants was the most appropriate for further research and development. The chemical profile of crude ethanol extracts of Marula stems and Sycamore leaves were determined using UPLC-Q-TOF-MS with MassLynx software. Eleven compounds have been tentatively identified in the ethanol extract of Marula stems of which four; quinic acid, catechin, epigallocatechin gallate (EGCg) and epicatechin gallate (ECg) have been confirmed using pure standards. Eight compounds were tentatively identified in the ethanol extract of leaves of the Sycamore tree of which five; palatinose, quinic acid, chlorogenic acid, rutin and isoquercetin have been confirmed using pure standards and four; vicenin-2, biflorin and isobiflorin have been confirmed through isolation, purification and structure elucidation using NMR. Palatinose, quinic acid, isobiflorin, chlorogenic acid, biflorin, vicenin-2 and quercetin-3-glucuronide have been identified for the first time in leaves of the Sycamore tree. Chemical profiles of ethanol extracts of Marula stems and leaves of the Sycamore tree were developed for quality control purposes allowing these to be used for further development with a potential for commercialization. The Marula stem ethanol extract was separately defatted, concentrated and then defatted-concentrated and the extract of Sycamore leaves was defatted by liquid-liquid partitioning. Screening of these extracts and Marula oil (purchased from a commercial supplier) in the anti-elastase and anti-collagenase assays revealed that the defatting-concentration step improved the anti-collagenase activity of the Marula extract. Further, the concentration and defatting-concentration steps lowered the colour intensity of the Marula stem ethanol extract and defatting lowered the colour intensity of the Sycamore leaf extract. Marula oil although traded as a cosmetic ingredient did not have any anti-collagenase or anti-elastase activity when bioassayed, anti-aging claims on products containing the oil are thus due to a different mode of action. The Marula stem ethanol extract was fractionated using a prep HPLC-UV to produce 23 fractions and leaves of the Sycamore tree produced 17 fractions after fractionation followed by screening of the fractions in the anti-elastase and anti-collagenase assays. Five Marula stem fractions exhibited good anti-collagenase activities (>80%) in the similar range as the positive control, EDTA. Chemical analysis of the active fractions using UPLC-MS revealed that EGCg and ECg were present in the fractions and may have contributed to their anti-collagenase activities. Upon screening the pure compounds in the collagenase assay, EGCg and ECg were as potent (p<0.05) as EDTA at 5 μg/ml. Thus, for the first-time EGCg and ECg have been shown to be the major compounds contributing to the collagenase inhibition activity of Marula stems and could be potentially developed into anti-aging ingredients. Similarly, three Sycamore fractions exhibited collagenase inhibition activity (>70%), chemical analysis of the active fractions revealed that isoquercetin contributed to the collagenase inhibition activities of the fractions. Screening of pure compounds at 10 μg/ml confirmed that isoquercetin exhibits anti-collagenase activity. This is the first report of anti-collagenase activity of isoquercetin, this report justifies further development of the compound as a cosmetic ingredient. In the anti-elastase assay, the ethanol extract of Marula stems and leaves of the Sycamore and their fractions showed activity. Upon screening of pure compounds from both plants, none of the compounds showed activity revealing that activity in the extracts and the fractions was due to synergistic effects. In conclusion, stable formulations of an anti-aging day cream and nourishing night cream were developed from combinations of the active, chemically characterized ethanol extracts of Marula stems and leaves of F. sycomorus for proof of concept. Further studies will be carried out beyond the scope of this study to evaluate the formulations for shelf life, compatibility, microbiology and dermal safety studies